Efektivitas Pengaturan Jarak Tanam dan Penyiangan Terhadap Pertumbuhan dan Produktivitas Tanaman Padi (Oriza sativa L.) Varietas IR 64 - Suherman Suherman; Supandji Supandji; Bambang Dwi Moeljanto; Nugraheni Hadiyanti (JINTAN : Jurnal Ilmiah Pertanian Nasional, 2021)
In plant cultivation, planting distance requires to be set so that the plants get enough living space to grow and develop. The purpose of the study was to study the effectiveness of spacing and weeding frequency on the productivity of rice (Oryza sativa L.) variety IR 64. The experiment was carried out from January to April 2020 in Ngrendeng, Gondang, Tulungagung. The experiment was in the form of a completely randomized block design with two factors. The first treatment of plant spacing consisted of 20x20 cm (J1), 20x25 cm (J2), and 20x30 cm (J3). The second treatment was the frequency of weeding, namely without weeding (P1), weeding at 17 days after planting/DAP (P2), and weeding at 17 and 30 DAP (P3). Data were analyzed using ANOVA and continued with the 5% Least Significant Difference test for a significant difference. The combination of spacing and frequency of weeding was known to increase the productivity of rice plants of the IR 64 variety. The growth of rice plants was significantly different, as seen from the variables of tillers and panicles formed, number of leaves, and plant height. The highest rice production was at a spacing of 20x25 cm and the frequency of weeding once at the age of 17 DAP, namely the weight of grain per clump of 43.99 gr, the number of productive tillers 20.33 stems, grain weight 34.88 gr; production of 2.41 kg/plot and production of 12.16 t/h.Â Usaha budidaya tanaman perlu pengaturan jarak tanam dan penyiangan gulma agar tanaman memperoleh ruang hidup yang cukup untuk tumbuh dan berkembang. Tujuan penelitian adalah mempelajari efektivitas pengaturan jarak tanam dan frekuensi penyiangan gulma terhadap produktivitas tanaman padi (Oryza sativa L.) varietas IR 64. Pelaksanaan penelitian dari bukan Januari sampai April 2020 di Ngrendeng, Gondang, Tulungagung. Percobaan dalam bentuk Rancangan Acak Kelompok Lengkap dengan dua faktor. Perlakuan kesatu jarak tanam terdiri 20x20 cm (J1), 20x25 cm (J2) dan 20x30 cm (J3). Perlakuan kedua adalah frekuensi penyiangan yaitu tanpa penyiangan (P1), penyiangan pada 17 hari setelah tanam/HST (P2), dan penyiangan pada 17 dan 30 HST (P3). Analisis data adalah anova dan dilanjutkan uji Beda Nyata Terkecil 5% apabila terdapat beda yang nyata. Kombinasi pengaturan jarak tanam dan frekuensi penyiangan dapat meningkatkan produktivitas tanaman padi varietas IR 64. Pertumbuhan tananam padi berbeda nyata terlihat dari variabel anakan dan malai yang terbentuk, jumlah daun, dan tinggi tanaman. Produksi padi yang tertinggi pada jarak tanam 20x25 cm dan frekuensi penyiangan sekali umur 17 HST yaitu berat gabah per rumpun sebesar 43.99 gr, jumlah anakan produktif 20.33 batang, berat bulir 34.88 gr; produksi 2.41 kg/petak dan produksi 12.16 t/ha.Â